The handbook of business discourse - Bargiela-Chiappini, Francesca (Edinburgh University Press, 2009)
The Handbook of Business Discourse is the most comprehensive overview of the field to date. It offers an accessible and authoritative introduction to a range of historical, disciplinary, methodological and cultural perspectives on business discourse and addresses many of the pressing issues facing a growing, varied and increasingly international field of research. The collection also illustrates some of the challenges of defining and delimiting a relatively recent and eclectic field of studies, including debates on the very definition of 'business discourse'. Part One includes chapters on the origins, advances and features of business discourse in Europe, North America, Australia and New Zealand. Part Two covers methodological approaches such as mediated communication, corpus linguistics, organisational discourse, multimodality, race and management communication, and rhetorical analysis. Part Three moves on to look at disciplinary perspectives such as sociology, pragmatics, gender studies, intercultural communication, linguistic anthropology and business communication. Part Four looks at cultural perspectives across a range of geographical areas including Spain, Brazil, Japan, Korea, China and Vietnam. The concluding section reflects on future developments in Europe, North America and Asia. Key Features Consists of newly commissioned chapters, authored by a vibrant group of internationally-known experts and emerging younger scholars, representing more than twenty countries. Individual chapters aim to offer breadth, depth and, where appropriate, illustrative analytical examples, and can be read as self-contained, mini-introductions to each topic. A valuable resource for students, researchers, teachers and trainers looking for a research-based, wide-ranging introduction to business discourse in a single volume. Endorsements: 'While many authors offer partial insights into business discourse, Francesca Bargiela-Chiappini has made a heroic effort to collect many such insights together in this impressive Handbook. The result is a rich volume that will become indispensable to students and scholars.' - Barbara Czarniawska, Professor of Management Studies, University of Gothenburg, Sweden 'Researchers interested in understanding and applying the various disciplinary approaches used to study business discourse will not be disappointed by The Handbook of Business Discourse. This much needed and welcome resource provides an authoritative set of up-to-date contributions from an impressive line-up of distinguished and emergent scholars.' - David Grant, Professor of Organizational Studies, University of Sydney